2013
DOI: 10.1017/s0033291713002158
|View full text |Cite
|
Sign up to set email alerts
|

Extremely preterm birth and adolescent mental health in a geographical cohort born in the 1990s

Abstract: ADHD was more prevalent in EP/ELBW adolescents than controls, which is consistent with some, but not all, reports on preterm survivors born before the 1990s, and younger preterm children born in the 1990s. The high rates of anxiety and mood disorders were similar in both groups, and comparable with population-based estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 68 publications
4
36
1
Order By: Relevance
“…As we have previously reported, EP/ELBW participants had a lower IQ than control participants [Cheong et al, 2013]. The groups were similar in terms of sex and history of most psychiatric disorders, although ADHD diagnoses were more prevalent in the EP/ELBW group than controls [Burnett et al, 2014].…”
Section: Demographics and Mental Illnesssupporting
confidence: 68%
See 1 more Smart Citation
“…As we have previously reported, EP/ELBW participants had a lower IQ than control participants [Cheong et al, 2013]. The groups were similar in terms of sex and history of most psychiatric disorders, although ADHD diagnoses were more prevalent in the EP/ELBW group than controls [Burnett et al, 2014].…”
Section: Demographics and Mental Illnesssupporting
confidence: 68%
“…The ADHD module of the Children's Interview for Psychiatric Syndromes [Weller et al, ] was used to assess ADHD (inattentive, hyperactive/impulsive, and combined subtypes). We have previously reported these outcomes in this cohort [Burnett et al, ] and diagnoses identified were primarily ADHD, mood disorders, and anxiety disorders.…”
Section: Methodsmentioning
confidence: 99%
“…There is also evidence of an increased risk for psychiatric disorders in adulthood, including ASD,59 ADHD62 63 and mood disorders59 64 65 demonstrating continuity with outcomes reported in childhood (figure 3). A number of studies have also reported reduced social interactions and risk-taking behaviours in VP/VLBW adolescents66 67 and higher introversion, autistic features and neuroticism which may underpin some of the social difficulties in this population.…”
Section: Outcomes In Adulthoodmentioning
confidence: 93%
“…However, on tasks that did not have normative data or standard scores for clinical impairment, we used a cut‐off equivalent to the 10th percentile of the full‐term control group. Detailed information about the control group characteristics and group differences for cognitive and psychiatric outcomes have been published elsewhere (Burnett et al ., ; Cheong et al ., ; Molloy, Wilson‐Ching, Doyle, Anderson, & Anderson, ; Molloy et al ., ; Wilson‐Ching et al ., ).…”
Section: Methodsmentioning
confidence: 99%